Misdiagnosis of malaria using wrong buffer substitutes for rapid diagnostic tests in poor resource setting in Enugu, southeast Nigeria (2014)
Background. A key to the effective management of malaria is prompt and accurate diagnosis, and the use of malaria rapid diagnostic tests (mRDTs) is becoming relevant in the absence of reliable microscopy. This study explored the phenomenon of using the wrong buffer vial (often a kit from another brand or buffer from HIV rapid test kits), dextrose, saline or distilled water among health care providers who used RDTs for malaria diagnosis in resource poor settings in Enugu South East, Nigeria. Materials and Methods. Laboratory personnel (medical laboratory scientists, technicians, assistants, nurses, community health extension workers (CHEW), community health officers (CHO) and doctors) were interviewed using structured questionnaires and results were checked using the SOP checklist. The selection criterion was a prior experience with using RDTs, and any facility that did not use RDTs was excluded. Results. Of the 80 study participants that completed their questionnaires, 56.3% reported that malaria diagnosis was positive using non-buffer RDTs detection while others reported negative results. Among the various professionals who used RDTs, 76.2% reported to have run out of RDT buffer stock at least once. Of the study participants that ran out of RDT buffer solution, 73% declared to have used non-RDT alternatives (physiological saline, 0.9% NaCl), distilled water, HIV buffer or ordinary water). Only 30% had received formal training on the proper usage and application of RDTs while 70% had never received any formal training on RDTs but learnt the technique of using RDT on the job. Conclusions. This study demonstrated that at least three quarters of health care workers in a resource poor setting had run out of buffer when using malaria RDTs and that the majority of them had used buffer substitutes, which are known to generate inaccurate tests results. This has the consequence of misdiagnosis, thus potentially damaging the credibility of malaria control.